Partisipasi Masyarakat dalam Perencanaan Pembangunan di Kampung Yoka, Distrik Abepura, Kota Jayapura - Nurak, Anitha; Bao, Bonefasius; Ayomi, Hendrik V.; Bakri, Hendry (Innovative: Journal Of Social Science Research, 2025)
This research seeks to explain the role of community participation in development, the active involvement of the community or participation can mean involvement in the process of determining the direction of the development policy strategy implemented by the government. In terms of planning, community participation as the frontline in the implementation of development can be seen during the implementation of the Village Development Planning Meeting (MUSREMBANG). This research design is descriptive research with a qualitative approach. The type of data used in this research is qualitative. Data collection techniques were carried out in several ways, namely interviews, observation and documentation. The results showed that community participation in development planning in kamung yoka has not been maximized. This is illustrated by the lack of interest and desire of the community to attend and play an active role in the Village Development Planning Meeting (MUSREMBANG)